2011
DOI: 10.1016/j.jdeveco.2010.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Common factors in Latin America's business cycles

Abstract: We develop a common factor approach to reconstruct new business cycle indices for Argentina, Brazil, Chile, and Mexico ("LAC-4") from a new dataset spanning 135 years. We establish the robustness of our indices through extensive testing and use them to explore business cycle properties in LAC-4 across outward-and inward-looking policy regimes. We find that output persistence in LAC-4 has been consistently high across regimes, whereas volatility has been markedly time-varying but without displaying a clear-cut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 38 publications
7
53
0
2
Order By: Relevance
“…Also, they should be taken into account when choosing a reference currency in a …xed exchange rate arrangement: "dollarisation" does not appear an obvious option. Aside from their scienti…c merits and policy implications, our …ndings that international risk sharing could be problematic at a regional level but it is still viable when capital crosses continents is consistent with the conclusions in Aiol… et al (2006) and may also be of bene…t to international investors.…”
Section: Introductionsupporting
confidence: 81%
“…Also, they should be taken into account when choosing a reference currency in a …xed exchange rate arrangement: "dollarisation" does not appear an obvious option. Aside from their scienti…c merits and policy implications, our …ndings that international risk sharing could be problematic at a regional level but it is still viable when capital crosses continents is consistent with the conclusions in Aiol… et al (2006) and may also be of bene…t to international investors.…”
Section: Introductionsupporting
confidence: 81%
“…Finally, the average effect of external factors (graph III in Panels A-F) is within a similar range to the one for the regional components (as also in Aiolfi et al 2010), continued its minimum and maximum values being those for Venezuela and Peru, respectively. As for the individual countries, the observed pattern for Argentina mirrors that of the country-specific component: The lowest value corresponds to the Argentine crisis, whilst the highest coincides with the first symptoms of the global crisis.…”
Section: Appendix: Evidence From La Individual Countriessupporting
confidence: 58%
“…Concerning regional factors (graph II in Panels A-F), there is evidence of a sizeable regional business cycle component in the LA countries, as also found by Aiolfi et al (2010) and Boschi and Girardi (2011), among others. Averaging over all simulation steps and rolling estimates, regional factors account from about 20 (in the case of Chile) to 40 per cent (for Venezuela) of output growth variability.…”
Section: Appendix: Evidence From La Individual Countriesmentioning
confidence: 54%
“…Despite that, they found that the inverted Latin American business cycle closely follows the U.S. business cycle. Aiolfi et al (2011) develop a dynamic common factor approach to reconstruct new business cycle indices for Argentina, Brazil, Chile, and Mexico from an unprecedentedly comprehensive dataset on sectorial output, trade, fiscal and financial variables spanning 135 years.…”
Section: Latin America Experiencementioning
confidence: 99%
“…Indeed, most business-cycle studies in Latin America relied on annual data, and the ones with quarterly data are the exception; see, for example, Engle and Issler (1993), Calvo et al (1992), Hecq et al (2006), and, more recently, Aiolfi et al (2011). Since business-cycle research worldwide is conducted using monthly data, the scarcity of reliable highfrequency databases in Latin America has been a key obstacle for business-cycle studies in the region as a whole and in individual countries.…”
Section: Introductionmentioning
confidence: 99%